Genetic evaluation of Ongole sires - Vinoo, R; Rao, G Narasimha; Gupta, B Ramesh; Rao, K Babu (The Indian Journal of Animal Sciences, 2005)
Data on 17 sires having at least 4 daughters per sire, born during 1988 to 2002 and maintained in the 4 Ongole cattle breeding farms located in the breeding tract at Lam, Mahanandi, Chadalawada and Chinataladevi of Andhra Pradresh were analyzed for evaluation based on the simple daughter average indxes, dairy search index and adjusted least-squares method using 305-day first lactation milk yield of their daughters. The sire indices obtained by simple daughter average index dairy search index and adjusted least squares method ranged from 304 to 665. 363 to 577 and 367 to 547 kg respectively. Positive and highly significant rank correlations indicated that these 3 methods of sire evaluation could be used with equal efficiency.